PEMBERDAYAAN USAHA KECIL MENENGAH (UKM) DARI PERSPEKTIF PENGANGGURAN (STUDI PADA KULINER DI BALI) - lasmi wayan (Jurnal Ilmiah Manajemen & Bisnis, 2016)
The purpose of this study was to determine the empowerment of SMEs of Culinary in Bali from the perspective of unemployment, voluntary unemployment either or forced unemployment. The method used in data collection, was the documentation with the help of a questionnaire. The design of the study was multiple linear regression analysis. From this analysis, the results showed that the empowerment of SMEs of Culinary in Bali was 4.3% on the unemployment rate. Judging from the two types of unemployment, namely voluntary unemployment and forced unemployment, where forced unemployment was more dominant of 2% of voluntary unemployment.